Peran Komunikasi Antarbudaya dalam Mengatasi Konflik Sosial Di Masyarakat Multikultural (Studi Pada Masyarakat Kecamatan Sukakarya Kabupaten Musi Rawas) - Alfarabi; Aldila Vidianingtyas Utami; Anis Endang Sri Murwani (STAI Bumi Silampari, 2025)
This study examines the role of intercultural communication in resolving social conflicts in multicultural societies, with a case study in the Sukakarya District community, Musi Rawas Regency. Amidst the increasingly complex dynamics of cultural diversity, differences in values, norms, and perceptions between community groups often trigger social conflicts. Intercultural communication is considered a strategic instrument that can create mutual understanding and reduce tensions that arise due to these differences. This study uses a qualitative approach with data collection methods through in-depth interviews, participant observation, and document analysis. The data obtained were analyzed thematically to identify communication mechanisms that have been implemented by the community in reducing conflicts, as well as to reveal supporting factors for the success of intercultural interactions. Initial findings indicate that empathy, adaptation, and appreciation for the cultural identity of each group play an important role in creating social harmony. The results of this study are expected to provide significant contributions to the development of effective intercultural communication models, as well as provide strategic recommendations for policy makers and communication practitioners in designing preventive and adaptive intervention programs. Thus, this study not only enriches academic discourse but also becomes a practical reference in efforts to strengthen social integration and reduce conflict in multicultural societies.